Application of multivariate statistical analysis in characterising the phenotypic variability of locally adapted Muscovy ducks (Cairina moschata) in Nigeria (2023)
While there are studies that describe the biometric traits and phenotypic variations in Muscovy ducks in Nigeria, there are limited studies that employ a multivariate approach to depict the phenotypic variability of Muscovy ducks in Nigeria. Therefore, this study aimed to explicate genetic variabilities within C. moschata using qualitative and biometric traits. This study used a multivariate statistical method to phenotypically characterise locally adapted Muscovy duck populations from seven ecogeographical locations in Ibadan, Nigeria. Four qualitative traits (eye colour, bill colour, bean colour and shank colour) and eleven biometric traits (head length, neck length, body length, wings length, shank length, toe length, thigh length, bill length, breast length, breast width and bodyweight) were evaluated in 201 ducks (109 males and 92 females). To study the possible effects of geographical locations on selected phenotypes, frequency distribution, univariate analysis, stepwise and canonical discriminant analyses and cluster analysis were performed. The association between body weight (BWT) and other biometric traits was assessed using the Pearson product-moment correlation coefficient. Male ducks (drakes) were generally more abundant than female ducks (hens). The most prevalent colour traits of locally adapted Muscovy ducks were brown eye colour (70.65 %), black bean colour (62.69 %), pinkish white bill colour (45.27%) and grey shank colour (56.22 %). Overall, ecogeographical location did not significantly affect (p < 0.05) the measured biometric traits. However, across all locations, the sexual dimorphism was favourable in male ducks, with respect to biometric traits. Stepwise-canonical discriminant analysis revealed a substantial intermixing of biometric traits, especially in Molete, Oje, Adogba and Ajibode ducks. Similarly, the cluster analysis, although it separated the birds into different clusters, showed some level of admixture. The small Mahalanobis distance (0.61-3.88) suggested that, with respect to location, there was more morphological similarity than dissimilarity between ducks. The correlation analysis revealed that the body weight of ducks can be fairly estimated from other biometric traits due to their positive, statistically significant correlation. In general, the ducks from all seven ecogeographical locations were rather homogeneous than heterogeneous.